Long-term standard sentinel node biopsy after neoadjuvant treatment in breast cancer: a single institution ten-year follow-up. Issue 4 (April 2021) - Kahler-Ribeiro-Fontana, Sabrina; Pagan, Eleonora; Magnoni, Francesca; Vicini, Elisa; Morigi, Consuelo; Corso, Giovanni; Intra, Mattia; Canegallo, Fiorella; Ratini, Silvia; Leonardi, Maria Cristina; La Rocca, Eliana; Bagnardi, Vincenzo; et al.
Abstract: Introduction: In patients with positive lymph nodes (cN+) prior to neoadjuvant treatment (NAT), which convert to a clinically negative axilla (cN0) after treatment, the use of sentinel node biopsy (SNB) is still debatable, since the false-negative rate (FNR) is significantly high (12.6–14.2%). The objective of this retrospective mono-institutional study, with a long follow-up, aimed to evaluate the outcome in patients undergoing NAT who remained or converted to cN0 and received SNB independent of target axillary dissection (TAD) or the removal of at least 3 sentinel nodes (SNs). Methods: This study analyzed 688 consecutive cT1-3, cN0/1/2 patients, operated at the European Institute of Oncology, Milan, from 2000 to 2015 who became or remained cN0 after NAT and underwent SNB with a least one SN found. Axillary dissection (AD) was not performed if the SN was negative. Nodal radiotherapy (RT) was not mandatory. Results: Axillary failure occurred in 1.8% of the initially cN1/2 patients and in 1.5% of the initially cN0 patients. After a median follow-up of 9.2 years (IQR 5.3–12.3), the 5- and 10-year overall survival (OS) were 91.3% (95% CI, 88.8–93.2) and 81.0% (95% CI, 77.2–84.2) in the whole cohort, 92.0% (95% CI, 89.0–94.2) and 81.5% (95% CI, 76.9–85.2) in those initially cN0, 89.8% (95% CI, 85.0–93.2) and 80.1% (95% CI, 72.8–85.7) in those initially cN1/2. Conclusion: The 10-year follow-up confirmed our preliminary data that the use of standard SNB is acceptable in cN1/2 patients who become cN0 after NAT and will not translate into a worse outcome.